2020
DOI: 10.5230/jgc.2020.20.e30
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Stage IB Gastric Cancer after Surgical Resection

Abstract: Purpose: The standard treatment for stage IB gastric cancer is curative surgery alone, but some patients show poor survival with disease recurrence after curative surgery. The aim of this study was to identify prognostic factors of recurrence and long-term survival in patients with stage IB gastric cancer after surgery. Materials and Methods: We retrospectively reviewed data from 253 patients with stage IB gastric cancer who underwent gastrectomy between 2011 and 2016 at Kyungpook National University Chilgok H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Moreover, most of the previous studies combined LI and VI together and investigated the effects of prognosis on lymphatic and vascular invasion together [ 22 24 ]. Individual studies of LI and VI are scattered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, most of the previous studies combined LI and VI together and investigated the effects of prognosis on lymphatic and vascular invasion together [ 22 24 ]. Individual studies of LI and VI are scattered.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the results were in accordance with their findings, and both LI and VI were predictors of survival. Moreover, most of the previous studies combined LI and VI together and investigated the effects of prognosis on lymphatic and vascular invasion together [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…De Marco et al reported that age did not have any significant influence on curative resections and long-term survival in patients with gastric cancer (23). In contrast to these conclusions, Park et al and Yu et al showed that older age was a prognostic factor for worse 5-year survival even for patients after gastric cancer resection with stage I according the TNM classification (22,25). Hsu et al performed a retrospective review of the cohort of patients with gastric cancer who underwent curative resection and found that older age was associated with a higher overall perioperative complications rate (p=0.035) and perioperative mortality rate (p=0.015).…”
Section: Discussionmentioning
confidence: 98%
“…However, evidence of the survival benefits of adjuvant chemotherapy for early gastric cancer is lacking. Although there is no lymph node metastasis in T2N0M0 gastric cancer, some patients still experience recurrence[ 10 - 16 ]. Therefore, it is important to identify patients with stage T2N0M0 gastric cancer who are at high risk of recurrence and may require adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…According to the 8th edition of the American Joint Committee on Cancer (AJCC) guidelines for gastric cancer, T2 was defined as tumor invasion of the muscularis propria[ 9 ]. It is controversial whether adjuvant chemotherapy is necessary for stage T2N0M0 gastric cancer[ 10 - 16 ]. Previous studies have suggested that patients with stage I gastric cancer cannot benefit from adjuvant chemotherapy[ 17 ].…”
Section: Introductionmentioning
confidence: 99%